Logarithmic function is the inverse of the exponential function. The logarithmic function that is equivalent to 2⁵ = 32 is log₂32=5.
<h3>What is the Logarithm function?</h3>
A log function is a way to find how much a number must be raised in order to get the desired number.
![a^c =b](https://tex.z-dn.net/?f=a%5Ec%20%3Db)
can be written as
![\rm{log_ab=c](https://tex.z-dn.net/?f=%5Crm%7Blog_ab%3Dc)
where a is the base to which the power is to be raised,
b is the desired number that we want when power is to be raised,
c is the power that must be raised to a to get b.
Given to us
2⁵ = 32
As we know that we can convert a number powered to another number therefore exponential function into a log function, thus,
![2^5 = 32\\\\\rm log_2 32 = 5](https://tex.z-dn.net/?f=2%5E5%20%3D%2032%5C%5C%5C%5C%5Crm%20log_2%2032%20%3D%205)
Hence, the logarithmic function that is equivalent to 2⁵ = 32 is log₂32=5.
Learn more about Logarithmic function:
brainly.com/question/7302008
Answer:
6 years
Step-by-step explanation:
So each person's age can be represented as a linear equation, since each year our age increases by 1. It can be represented in the slope-intercept form: y=mx+b. The slope in this case is going to be 1, since the time is going to be years, and each year everyone's age goes up by 1 (of course if you're still alive...) and y-intercept in this case represents their current age.
So the father can be represented as: y=x+38
The sons can be represented as: y = x+13 and y=x+5
The daughter can be represented as: y=x+8
So adding up all his children you get:
(x+13)+(x+5)+(x+8)
This gives you the equation:
3x+26
Now set this equal to the father's age to solve for x (in this context it's years)
3x+26=x+38
Subtract from both sides
2x+26=38
Subtract 26 from both sides
2x=12
Divide both sides by 2
x=6
So in 6 years the father will be the same age as his children put together
Answer:
7
Step-by-step explanation:
f(g(2))
f(x+4) and you would replace x with two, so you would get
f(2+4) = f(6)
You would then plug in 6 for the x in the f(x) equation:
2(6) - 5 = 12-5 = 7